Growth analysis in cumin (Cuminum cyminum L.) under different weed control methods and nitrogen levels - Sharma, S S Yadav, O P (Journal of Spices and Aromatic Crops, 2004)
A field experiment was conducted at Jobner (Rajasthan) to evaluate the effect of weed control and nitrogen application on growth and yield of cumin (Cuminum cyminum). The study revealed that two hand weedings done at 25 and 50 days after sowing (DAS) yielded maximum seeds (5.50 q ha-1) which was 292.7% higher over control (with weeds). This treatment also attained maximum harvest index (40.7%), crop growth rate during 40-70 DAS and 70 DAS and relative growth rate during 40-70 DAS phase. Trifluralin @ 1.08 kg ha-1 (pre-plant incorporation) also increased seed yield by 252.9% which was the next superior herbicidal treatment with regard to yield and physiological parameters. Application of 45 kg N ha-1 was the most effective dose with regard to seed yield, crop growth rate and relative growth rate and was on par with 30 kg-N ha-1. Seed yield had a significant and positive association with growth, yield attributes and nutrient uptake by the crop.